Positive BRAFV600E mutation of primary tumor influences radioiodine avidity but not prognosis of papillary thyroid cancer with lung metastases - Huang, Shuhui; Qi, Mengfang; Tian, Tian; Dai, Hongyuan; Tang, Yuan; Huang, Rui (Frontiers in Endocrinology, 2022)
Purpose: This study investigated the relationship between BRAFV600E mutation of primary tumor and radioiodine avidity in lung metastases (LMs), then further evaluated the impact of BRAFV600E mutation and radioiodine avidity status on the prognosis of papillary thyroid cancer (PTC) with LMs. Methods: Ninety-four PTC patients with LMs after total-thyroidectomy and cervical lymph node dissection between January 2012 and September 2021 were retrospectively included. All patients received BRAFV600E mutation examination of primary tumors and radioiodine therapy (RAI). The therapeutic response was evaluated by Response Evaluation Criteria in Solid Tumors (RECIST) assessments (version 1.1). For patients with target lesions, response was divided into complete response (CR), partial response (PR), stable disease (SD) and progress disease (PD); for patients without target lesions, CR, non-CR/non-PD and PD were divided. In this study, PR and SD were classified as non-CR/non- PD for analysis. Chi-square test and logistic regression were used to analyze the impact factor on PD and mortality. PFS and OS curves were constructed by the Kaplan–Meier method. Results: 21.2% (7/33) of patients with positive BRAFV600E mutation and 62.3% (38/61) of patients with negative BRAFV600E mutation had radioiodine avid LMs (χ2=10.632, P=0.001). Patients with positive BRAFV600E mutation are more likely to be losing radioiodine avidity; the odds ratios (ORs) were 5.323 (95% CI: 1.953-14.514, P=0.001). Among patients with radioiodine-avid LMs, all patients (7/7) with positive BRAFV600E mutations remained non-CR/non-PD, as for patients with BRAFV600E negative mutation, the rates of CR, non-CR/non-PD and PD were 0% (0/35), 91.4% (32/35), and 8.6% (5/35), respectively (P=1.000). Finally, 25 patients were PD, and 6 patients were dead, loss of radioiodine avidity was the independent predictor for PFS, the odds ratios (ORs) were 10.207 (95% CI: 2.629-39.643, P=0.001); while BRAFV600E mutation status was not correlated with PFS (P=0.602). Similarly, BRAFV600E mutation status was not correlated with OS, only loss of radioiodine avidity was the factor associated with OS in univariate analysis. Conclusion: LMs of PTC were more likely to losing radioiodine avidity when primary tumor had positive BRAFV600E mutation, however, only radioiodine avidity not BRAFV600E mutation status affected the clinical outcome of patients with lung metastatic PTC.